Semi-automatic pistols on cotton, cotton polyester blend, satin and jersey fabric in relation to firing distance - Shapihi, Siti Salha (Universiti Sains Malaysia, 2015)
Firearm-related crime is classified as violent crime and surely it has given an impact to general public safety. Study of gunshot residue (GSR) becomes important in investigating shooting incidents. Detection of GSR can estimate firing distances. This study focused on GSR distribution pattern deposited on four different types of fabrics, shot at three distances by four different types of pistols. 9 mm pistols and 9 mm ammunition were used in test firing. All shooting tests were performed at Ibu Pejabat Polis Daerah (IPD) Kota Bharu, Kelantan. Physical observation, microscopic examination and chemical enhancement methods were used in detection of GSR. Results showed that, as shooting distance increased, GSR particles decreased and dispersed widely. There was not much difference in diameter of bullet and soot if the shooting distance more than 1 m. For close range shot, GSR distribution pattern was quite useful to characterise the pistol used but not strong enough to identify pistol. As muzzle-to-target increased, type of pistol cannot be determined because the result showed no observable difference in term of GSR pattern and bullet hole diameter. Chemical enhancement involving the application of Modified Griess Test (MGT) in detection of nitrite residues as a by-product of combustion of gunpowder was performed. The presence of dark-purple colour indicated positive result of nitrite. Careful examination showed the decrease in the intensity of the colour in which the colour was too fade to observe as the shooting distance increased. Nitrite can still be detected up to 3 m on some fabric used and certain type of pistols. It is believed that, different pistols act differently during firing the cartridge and discharge the GSR. Mesh size of fabric is important in attachment persistency of residues. GSR distribution pattern from 9 mm semi-automatics pistols on fabrics could be established by visual and chemical enhancement method.